2016
DOI: 10.2147/ijn.s100903
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis inducing ability of silver decorated highly reduced graphene oxide nanocomposites in A549 lung cancer

Abstract: Recently, graphene and graphene-based materials have been increasingly used for various biological applications due to their extraordinary physicochemical properties. Here, we demonstrate the anticancer properties and apoptosis-inducing ability of silver doped highly reduced graphene oxide nanocomposites synthesized by employing green approach. These nano composites (PGE-HRG-Ag) were synthesized by using Pulicaria glutinosa extract (PGE) as a reducing agent and were evaluated for their a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…For example, in the A549 cell line, the implication of graphene nanopores in the induction of early apoptosis was described and, at concentrations higher than 250 mg L −1 , late apoptosis was observed too [48]. In addition, Adil et al observed that apoptosis can be triggered by green synthesized nanocomposites of silver-decorated highly reduced graphene oxide [49], while Mbeh et al described that high concentrations of graphene oxide nanoribbons (100 mg L −1 ) can also cause cell apoptosis [50]. However, other authors did not find any evidence of apoptosis induction in A549 cells after treatment with GO derivatives.…”
Section: Determination Of Human Cancer Cell Line A549 Response To Go mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in the A549 cell line, the implication of graphene nanopores in the induction of early apoptosis was described and, at concentrations higher than 250 mg L −1 , late apoptosis was observed too [48]. In addition, Adil et al observed that apoptosis can be triggered by green synthesized nanocomposites of silver-decorated highly reduced graphene oxide [49], while Mbeh et al described that high concentrations of graphene oxide nanoribbons (100 mg L −1 ) can also cause cell apoptosis [50]. However, other authors did not find any evidence of apoptosis induction in A549 cells after treatment with GO derivatives.…”
Section: Determination Of Human Cancer Cell Line A549 Response To Go mentioning
confidence: 99%
“…Also, the toxicological potential of other carbon nanomaterials toward S. cerevisiae was reported, such as multi-walled carbon nanotubes (MWCNTs) or oxidized single-walled carbon nanotubes (O-SWCNTs), which induced significant yeast mortality at 400 mg L −1 (6.1%) and 188.2 mg L −1 (approximately 11%) respectively [53,54]. 49.7% when the material was present at the higher concentration. In contrast, GOC showed no significant influence on the yeast viability at 160 mg L −1 , although the viability loss observed at the higher concentration was very similar for both nanomaterials.…”
Section: Determination Of Saccharomyces Cerevisiae Cells Response To mentioning
confidence: 99%
“…Apoptosis is considered as programmed cell death orchestrated by cascade of interdependent synchronised cellular events. It is the most critical process for maintenance of homeostasis, where an efficient balance between cell proliferation and cell death is maintained [ 50 ]. Fabrication of apoptotic nanoinducers is of prime importance to develop novel nanomedicine against cancer.…”
Section: Resultsmentioning
confidence: 99%
“…Based on several reports on nanotoxicology, both graphene and semiconductive nanomaterials such as ZnO NPs are very much effective to sensitize the elevated level of ROS production within the cells that ultimately results in cell death. Hence, the present work utilized both graphene and ZnO NPs decorated on rGO nanocomposites to test their anticancer activity. The molecular mechanisms between ROS generation/oxidative stress and NP-mediated cell death are well studied. In brief, the synthesized rGO/ZnO-NC are highly effective in the generation of ROS species within the cancer cells at low or moderate levels, which affects the signal transmission and cell proliferation rates, whereas at high concentration ratios, it leads to the modification of lipids and proteins and damage of DNA.…”
Section: Discussionmentioning
confidence: 99%